Keeping Families Together: Companion Animals as a Public Health Imperative - Lori R Kogan; Rebecca Niemiec (Journal of One Health Systems, 2026)
Contemporary US public health frameworks emphasize social, economic, and environmental determinants of health, yet largely overlook the reality that most households include companion animals regarded as family members. This omission has tangible consequences during crises such as housing instability, illness, domestic violence, or disasters, when families are often forced to choose between their own safety and the safety of their animals. We argue that this represents a significant public health failure. Drawing on interdisciplinary evidence, we propose that companion animals function as a social determinant of health, that forced separation constitutes a public health harm, and that Human-Animal Support Services (HA/SS) should be recognized as essential public health infrastructure. We conclude with a call to integrate companion animals into public health research, policy, education, and cross-sector infrastructure investment.
Keywords: Companion animals; Social determinants of health; Forced separation; Human-Animal Support Services; Public health policy